2015
DOI: 10.1016/j.scr.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-frequency electromagnetic field on human bone marrow stem/progenitor cell differentiation

Abstract: Human bone marrow stromal cells (hBMSCs, also known as bone marrow-derived mesenchymal stem cells) are a population of progenitor cells that contain a subset of skeletal stem cells (hSSCs), able to recreate cartilage, bone, stroma that supports hematopoiesis and marrow adipocytes. As such, they have become an important resource in developing strategies for regenerative medicine and tissue engineering due to their self-renewal and differentiation capabilities. The differentiation of SSCs/BMSCs is dependent on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 104 publications
4
125
0
1
Order By: Relevance
“…In the sinusoidal electric field the value of the current in the body increases with the magnitude of the frequency [4]. ELF magnetic field has biological effects such as, inducing cell metabolism [3], altering chemical or enzyme processes (Agustrina, 2013: 405-412), and altering membrane surface properties [13]. The ability of the biological effects of the magnetic field to affect the permeability of the ion channels in the membrane can give the effect of ion transport into the cell and give changes to the organism [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the sinusoidal electric field the value of the current in the body increases with the magnitude of the frequency [4]. ELF magnetic field has biological effects such as, inducing cell metabolism [3], altering chemical or enzyme processes (Agustrina, 2013: 405-412), and altering membrane surface properties [13]. The ability of the biological effects of the magnetic field to affect the permeability of the ion channels in the membrane can give the effect of ion transport into the cell and give changes to the organism [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that HSCs migrate during embryonic development and early childhood; the migration of HSCs allows different sites to participate in hematopoiesis at different moments in life [184,185]. Importantly, numerous investigations have shown that ELF-EMFs can stimulate the division of stem cells and promote tissue regeneration [34,[186][187][188][189][190][191][192]. In addition, cell migration is regulated by physiological electric currents [123,[193][194][195], and ELF-EMFs are known to induce electric currents that can alter cell migration [34,88,191,192,[196][197][198].…”
Section: The Stem Cell Division Theory Of Cancer Provides a New Framementioning
confidence: 99%
“…Numerous investigations have shown that ELF-EMFs can stimulate the division of stem cells [37][38][39][40][41]. It is well established that exposure to ELF-EMFs results in induction of electric fields and associated currents in tissues, an effect that has been used to promote tissue regeneration [1,42,43].…”
Section: Elf-emfs May Increase the Risk Of Childhood Leukemia By Prommentioning
confidence: 99%
“…This effect has been observed with relatively weak magnetic fields (µT and mT) [1,44]. Since the division of stem cells is crucial for tissue regeneration, it is not surprising that ELF-EMFs can stimulate the division of stem cells of a variety of tissues [37][38][39][40][41].…”
Section: Elf-emfs May Increase the Risk Of Childhood Leukemia By Prommentioning
confidence: 99%